Pemikiran Muhammad Abduh tentang Politik Hukum, Tauhid, Sosial, dan Pendidikan - Umar Faruq Thohir (HUMANISTIKA : Jurnal Keislaman, 2020)
Modernization in the field of education is the most important part of social, economic, politic law, and aqeedah. That is, to build a modern society order, education is a very important aspect as a medium for the transformation of cultural values and knowledge. As stated by Belling and Toten that education is an instrument in modernization that is easier than modernization in the form of capital to buy technology. Education will encourage the development of intelligence and cultural products of society. The opinion of Belling and Toten clearly implies that investment in human resources through education will be more promising than in the form of capital to buy technology.